SIMPLE ADDITIVE WEIGHTING IN THE PROSPEROUS COOPERATIVE LOAN ELIGIBILITY SYSTEM OF FATMAWATI HOSPITAL - Handayani, Indah Puspasari; Rusdah, Rusdah; Pradana, Rizky; Irawati, Riri (Universitas Budi Luhur, 2024)
The era of industry 4.0 and society 5.0 is a social and economic alteration whose activities are gradually being integrated into technology which continues to be developed with the hope that information can be easily accessed effectively and efficiently according to needs. However, technological developments put pressure on the economy to continue to update the technological facilities it has. Cooperatives are an alternative for their members to improve their economy by taking out loans because the interest rates are quite low. Difficulty determining whether or not giving a loan is appropriate and subjectivity is often found in decision making that occurs at the Fatmawati Hospital Sejahtera Cooperative, there is a need for a decision support system using a simple additive weighting method that can bring about precise, accurate and efficient decisions in terms of time, through several alternatives. obtained from processing data and information with the results of a weighted sum resulting from the performance rating for each alternative contained in the criteria. In its implementation, the decision support system is quite valid and reliable by managers as can be seen from the TAM test results with an average perceived ease of use result of 0.971 in the validity test and 0.979 in the reliability test, as well as an average perceived usefulness result of 0.911 in the test. validity and 0.928 in the reliability test because the test results are above the validity and reliability score of the r table (0.754).